(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This scientific article explores the issues of accelerating digital transformation processes, widely introducing financial technologies (FinTech), and increasing the accessibility of banking services in commercial banks of the Republic of Uzbekistan. The dynamics of digitalization, neo-banks, and mobile application development in the country’s banking system are analyzed, highlighting existing challenges and solutions. Based on the study, scientific and practical recommendations are formulated to develop digital ecosystems and ensure cybersecurity in commercial banks.